Saltwater Fish Powder for Amelogenesis in Zebrafish Larvae (Danio rerio) - Christiono, Sandy; Pradopo, Seno; Hutami, Islamy Rahma; Indasari, Novia; Nurhapsari, Arlina; Rochmah, Yayun Siti Rochmah; Ibrahim, Zurairah; Yuniar, Savira Nurazky; Suparmi (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Graphical Abstract Highlight Research 1. The saltwater fish powder is rich in omega3, vitamin D, and calcium which helps tooth amelogenesis. 2. LC50 Toxicity Test was carried out using zebrafish larvae (Danio rerio) with negative control, positive control using 3,4-dichloroanilin, and treatment groups with saltwater fish powder solution in 6 different concentration. 3. No signs of zebrafish embryo mortality or developmental abnormalities on treatment group from the lowest (125Î¼g/ml) nor highest concentration (4000Î¼g/ml). 4. Saltwater fish powder has proven lack of toxicity. Abstract Many nutrients found in saltwater fish are thought to promote amelogenesis in ameloblast cells during tooth development. Although its toxicity is uncertain, saltwater fish powder provided benefits for amelogenesis. Zebrafish embryos have complex metabolic pathways and comprehensive physiological reactions. The LC50 toxicity of saltwater fish powder on zebrafish embryos was investigated in this study. The aim of the of the study is to determine the effect of LC50 toxicity on saltwater fish powder on zebrafish embryos. The experimental research method was a post-test-only control group design, consisting of eight groups, namely the negative control and the internal group using embryo media, the positive control using 3,4-dichloroanillin, and the treatment group 125Î¼g / ml, 250Î¼g / ml, 500Î¼g / ml, 1000Î¼g / ml, 2000Î¼g / ml, and 4000Î¼g / ml using 384 zebrafish embryos. Saltwater fish powder is diluted and observed for 96 hours, controlled every 24 hours. It was found that saltwater fish powder was not toxic because there were no dead zebrafish embryos from various concentrations, negative control, and internal control.